Isotopic ratios for C, N, Si, Al, and Ti in C-rich presolar grains from massive stars. Issue 2 (8th September 2022) - Schofield, Jordan; Pignatari, Marco; Stancliffe, Richard J; Hoppe, Peter
ABSTRACT: Certain types of silicon carbide (SiC) grains, e.g. SiC-X grains, and low density (LD) graphites are C-rich presolar grains that are thought to have condensed in the ejecta of core-collapse supernovae (CCSNe). In this work, we compare C, N, Al, Si, and Ti isotopic abundances measured in presolar grains with the predictions of 21 CCSN models. The impact of a range of SN explosion energies is considered, with the high energy models favouring the formation of a C/Si zone enriched in 12 C, 28 Si, and 44 Ti. Eighteen of the 21 models have H ingested into the He-shell and different abundances of H remaining from such H-ingestion. CCSN models with intermediate to low energy (that do not develop a C/Si zone) cannot reproduce the 28 Si and 44 Ti isotopic abundances in grains without assuming mixing with O-rich CCSN ejecta. The most 28 Si-rich grains are reproduced by energetic models when material from the C/Si zone is mixed with surrounding C-rich material, and the observed trends of the 44 Ti/ 48 Ti and 49 Ti/ 48 Ti ratios are consistent with the C-rich C/Si zone. For the models with H-ingestion, high and intermediate explosion energies allow the production of enough 26 Al to reproduce the 26 Al/ 27 Al measurements of most SiC-X and LD graphites. In both cases, the highest 26 Al/ 27 Al ratio is obtained with H still present at X H ≈ 0.0024 in He-shell material when the SN shock is passing. The existence of H in the former convective He-shell points to late H-ingestion events in the last days before massive stars explode as a supernova.